2014
DOI: 10.4314/thrb.v16i3.3
|View full text |Cite
|
Sign up to set email alerts
|

Predicting small mammal and flea abundance using landform and soil properties in a plague endemic area in Lushoto District, Tanzania

Abstract: Small mammals particularly rodents, are considered the primary natural hosts of plague. Literature suggests that plague persistence in natural foci has a root cause in soils. The objective of this study was to investigate the relationship between on the one hand landforms and associated soil properties, and on the other hand small mammals and fleas in West Usambara Mountains in Tanzania, a plague endemic area. Standard field survey methods coupled with Geographical Information System (GIS) technique were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…Most of the studies generally identified elevation to be the main factor influencing flea diversity, with an impact on factors such as rainfall, climate, habitat and environmental productivity, alongside anthropogenic influences (Benton and Altmann, 1964; Gong et al ., 2005; Eisen et al ., 2012; Meliyo et al ., 2014; Maestri et al ., 2017). Between the Pannonian Plain and the base of the Carpathian Mountains, air temperature falls and precipitation rises like it does in other increasing elevational diversity gradients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies generally identified elevation to be the main factor influencing flea diversity, with an impact on factors such as rainfall, climate, habitat and environmental productivity, alongside anthropogenic influences (Benton and Altmann, 1964; Gong et al ., 2005; Eisen et al ., 2012; Meliyo et al ., 2014; Maestri et al ., 2017). Between the Pannonian Plain and the base of the Carpathian Mountains, air temperature falls and precipitation rises like it does in other increasing elevational diversity gradients.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, our study found flea diversity growing during the spring as elevation increased, but no data were available to us for elevations above 1250 m. Nonetheless, a continual rise in the higher elevations along the gradient is unlikely from what is known in studies conducted at mountains in Africa (Eisen et al ., 2012; Meliyo et al ., 2014). This is especially due to the growing diversity of both the fleas and the hosts (Eisen et al ., 2012; Meliyo et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, for some hosts, mean flea abundance increased with an increase in mean annual air temperature/proximity to equator, while for others the abundance decreased with altitude (Linardi & Krasnov, 2012). Another contrasting study found that the abundance of fleas increased with elevation (Meliyo et al , 2014). In our study, lower values of flea prevalence and abundance were observed in the areas with higher elevations (such as the Humid Steppe region, see table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Statistical models help to determine the relative contribution of drivers to map vector occurrence or predict future vector distributions based on expected climate change [18]. In East Africa, scientists have had ample experience in surveying the bacterium Yersinia pestis, the causative agent of the plague, through GIS and Remote Sensing (RS) procedures [19][20][21][22][23]. However, so far only Beugnet et al [14] have modelled the distribution of the cat flea affecting pets based on climate forecasts for a large geographical area [14].…”
Section: Introductionmentioning
confidence: 99%